2022
DOI: 10.1088/1742-6596/2217/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the number of blades on diffuser unsteady loss of centrifugal pump

Abstract: In recent years, an unshrouded impeller is being developed for rocket turbopumps to reduce production costs and disk friction losses. However, the internal flow structure in a diffuser influenced by an impeller has not been clarified yet. In this study, we focused on the investigation of unsteady flow in turbopumps with unshrouded impellers and vaned diffusers by experiments and CFD. Furthermore, we investigated the effect of changing the number of blades of the impeller and diffuser on the unsteady losses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…When the liquid in a single flow channel connects to the diffuser along the tangential direction, it is discharged [9,10]. Ueda et al [11] investigated the impact of impeller blade number on pump performance through simulation and experimentation. They found that as the number of blades increases, the flow velocity fluctuations in the pump decrease in frequency, and the flow path becomes smaller, leading to an increase in losses within the pump.…”
Section: Introductionmentioning
confidence: 99%
“…When the liquid in a single flow channel connects to the diffuser along the tangential direction, it is discharged [9,10]. Ueda et al [11] investigated the impact of impeller blade number on pump performance through simulation and experimentation. They found that as the number of blades increases, the flow velocity fluctuations in the pump decrease in frequency, and the flow path becomes smaller, leading to an increase in losses within the pump.…”
Section: Introductionmentioning
confidence: 99%